The Effect of Corruption and Crime on GDP´s growth: The Latin American Case - Guillen, Jorge (Journal of Ecohumanism, 2024)
This paper analyzes the effect of Corruption and Crime in the GDP growth for a sample of 10 countries in Latin America. Some of the countries in the sample are mostly oriented to the left political party characterized by applications of protective economic policies while other countries are oriented to the right political policies with high degree of economic openness. The paper analyses countries like: Argentina, Bolivia, Brazil, Chile, Colombia, Equator, Costa Rica, Mexico, Peru and Venezuela. The countries oriented to protective economic policies with low degree of economic openness are Argentina, Bolivia, Equator, Mexico and Venezuela. In contrast, countries oriented to non-protective economic policies with high degree of economic openness are Brazil, Chile, Colombia, Costa Rica and Peru. The estimated relationship between Corruption, Crime and GDP growth take into account the country´s degree of openness.